The role of long-term psychodynamic psychotherapy in improving attachment patterns, defense styles, and alexithymia in patients with depressive/anxiety disorders - Khademi,Mojgan (2019)
Abstract Introduction Long-term psychodynamic psychotherapy (LTPP) emphasizes the centrality of intrapsychic and unconscious conflicts and their relation to development. Although there is evidence supporting the efficacy of LTPP in mental disorders, little research has been published on the efficacy of LTPP for depressive and anxiety disorders. Objective To examine whether patients with anxiety and depressive disorders demonstrate improvement in their attachment styles, defense styles, psychiatric symptoms, anxiety/depressive symptoms, and alexithymia with LTPP. Methods In this retrospective, descriptive study, the psychological outcomes of patients who were treated at the psychoanalytic clinic of Babol University of Medical Sciences were assessed. Fourteen patients diagnosed with depressive or anxiety disorder participated in the study of LTPP using the self-psychology approach. The Beck Depression Inventory II, Beck Anxiety Inventory, Adult Attachment Scale, 40-item Defense Style Questionnaire, and the 20-item Toronto Alexithymia Scale were administered at pre-treatment, post-treatment, and 6-month follow-up. Generalized estimating equations were used to analyze changes in psychological outcomes after each of the three assessments. Results The mean scores of depression and anxiety and secure attachment improved significantly after LTPP with self-psychology approach from baseline to post-treatment and follow-up. Also, the mean scores of neurotic and immature defenses, difﬁculty in identifying feelings, difﬁculty in describing feelings, externally oriented thinking, and total alexithymia scores decreased significantly from baseline to post-treatment and follow-up. Conclusion Symptoms of anxiety disorders, depressive disorders, insecure attachment styles, alexithymia, and neurotic/immature defense styles improved after the LTPP with self-psychology approach. Moreover, the improvements persisted at the 6-month follow-up.